Chronic Rhinosinusitis and Concomitant Medical Disorders - Gudis, David (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
It is with great pleasure that we present to you this Special Issue of Medical Sciences. In this issue, we present a comprehensive and contemporary review of the medical comorbidities that contribute to chronic rhinosinusitis, and, conversely, how our interventions as otolaryngologists can impact those systemic conditions. Our understanding of chronic rhinosinusitis has evolved tremendously over the last two decades. As we have learned, chronic rhinosinusitis-a chronic inflammatory condition of the nasal cavity and paranasal sinuses-is often a local inflammatory response to a systemic or mucosal disorder. The underlying systemic medical conditions not only influence the presentation and diagnosis of chronic rhinosinusitis, but also modify the patients' response to medical and surgical interventions. Chronic rhinosinusitis associated with cystic fibrosis, for example, is a disorder quite distinct from that associated with aspirin-exacerbated respiratory disease. A clear understanding of the nuances that distinguish these unique and challenging disorders is critical for the practicing otolaryngologist. Equally important, however, is a clear understanding of the powerful benefits that our interventions as otolaryngologists can have for our patients' rhinologic and systemic health. Knowing that our rhinologic interventions might spare an asthma patient a trip to an emergency room or reduce lung infections in a cystic fibrosis patient makes this a very exciting time to be a rhinologist. We hope you enjoy this Special Issue of Medical Sciences.